Effects of Dietary Inclusion of Shrimp Paste on Growth Performance, Digestive Enzymes Activities, Antioxidant and Immunological Status and Intestinal Morphology of Hybrid Snakehead (Channa maculata ♀ × Channa argus ♂) - Fang, Haohang; Xie, Jiajun; Liao, Shiyu; Guo, Tianyu; Xie, Shiwei; Liu, Yongjian; Tian, Lixia; Niu, Jin (Frontiers in Physiology, 2019)
A nutritional feeding experiment was conducted to evaluate the effects of shrimp paste on feeding attractiveness, growth performance, digestive enzyme activities, immune-related genes and intestinal morphologyin hybrid snakehead (Channa maculata ♀ × Channa argus ♂). Two diets were formulated with or without shrimp paste supplementation (D1：0% and D2: 3%) to feed fish for 8 weeks. Results showed that growth performance (FBW, WG and SGR) and feed intake significantly increased with shrimp paste supplemented (P<0.05), while FCR and SR of hybrid snakehead fed diets supplemented with shrimp paste or not showed no significant difference (P>0.05). Gut lipase and amylase activity was significantly higher in diet supplemented with shrimp paste than that in control group (P<0.05). Hepatic antioxidant statuses of hybrid snakehead fed dietary shrimp paste or not showed no significant differences in total antioxidant capacity, malondialdehyde and superoxide dismutase of fish (P>0.05). Results showed that feeding diet with shrimp paste supplemented did not significantly up-regulate expression of GR, IκB, P65 and IL8 (P>0.05). There are significantly more goblet cells in shrimp paste supplemented diet than that in control diet (P<0.05). However, villi length and muscle thickness showed no significant difference compared to control diet (P>0.05). The results indicated that dietary 3% shrimp paste supplementation improved the growth performance of hybrid snakehead by enhancing feed intake while made no difference to antioxidant capacity.